Integrasi Al-Qur’an, Qira’at, dan Tajwid: Telaah Relasi Konseptual dan Fungsional - Hilmy Pratomo Pratomo (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This article examines the conceptual and functional relationship between the Qur’an, qiraat, and tajwid as three integral entities in Qur’anic studies. The Qur’an is understood as the speech of Allah revealed to Prophet Muhammad, transmitted through mutawatir narration, and serving as the primary guidance for Muslims. Qiraat represent authentic variants of Qur’anic recitation with continuous chains of transmission back to the Prophet, affirming a plurality of readings within the framework of divine revelation. Tajwid, meanwhile, is positioned as the discipline that preserves the beauty, accuracy, and authenticity of recitation through phonetic rules directly inherited from the Prophet by oral transmission. Using a qualitative-descriptive approach based on library research, this study concludes that conceptually, the Qur’an constitutes the divine text, qiraat represent the transmission variants, and tajwid is the science of pronunciation. Functionally, the Qur’an is the object of recitation, qiraat safeguard its mutawatir diversity, and tajwid ensures phonetic precision and aesthetic quality. This triadic relationship demonstrates the epistemological and functional continuity by which Allah preserves the purity of the Qur’an across generations.